(untitled) (Herald of Journalism, 2018)
The author analyzes trends in the development of world and national television journalism from the point of view of new media. The Internet have an important role of the information and communication function of the entire media system, which leads to a change in the attitude towards modern journalism with facts and arguments. The author considers the best practices of television programs of such worldfamous news agencies as the BBC, Al Jazeera and television of India, as criteria for the authenticity of domestic television channels. It also emphasizes the need for personal trainings, special courses aimed at increasing the professionalism of professionals in the field of digital technology, live broadcast and training for freelancers. Within the framework of the research, the author gives an interpretation of the concept of information potential, information space, information monitoring, television image, television ratings, telecritics. In the training of professional specialists from the national information space to the world level, the experience of the Eurasian National University is being studied. Gumilev and Russia. At the moment, along with the diploma, experience and qualifications are of particular importance, and their competitiveness is evaluated in the same sense. For the new media era, the author believes that today’s television studio, creative thinker, full-featured broadcasting company and modern technical equipment is an indicator of time.